Protection of Self-Employed Workers in the Light of United Nations and International Labour Organisation Acts – Conclusions of the National Science Centre Research Project No. 2018/29/B/HS5/02534 - Duraj, Tomasz (Acta Universitatis Lodziensis. Folia Iuridica, 2024)
The purpose of this article is to present the most important areas of protection for the self-employed under UN and ILO law, as well as their relevance for national legal orders. This is in reference to the conclusions of the National Science Centre research project No. 2018/29/B/HS5/02534. Due to the limited framework of the article, the author only highlights the most important issues concerning the title issue.